Antibiotic Resistance and Virulence Gene Profiles of Vibrio parahaemolyticus, Vibrio cholerae, and Vibrio alginolyticus Isolated from Commercial Shrimp Farm in Kuching, Sarawak - Elexson, Nillian; EASTERINA EMPINA, EDWIN; Dalene, Lesen; Manju, Stephen; Mastura, Sani (UNIMAS Publisher, 2025)
In the management and treatment of Vibrio spp. infections in aquaculture, antibiotics have traditionally been used. Misuse of antibiotics, however, has led to the emergence of resistance strains. In this study, antibiotic susceptibility testing of 30 (n=30) Vibrio spp. isolates were performed by using 18 antibiotics, revealing resistance to at least two antibiotics. Antibiotics Ceftazidime, Meropenem, Gentamicin, Tetracycline, Nalidixic acid, Norfloxacin, Ciprofloxacin, and Chloramphenicol were 100% effective against all isolates of V. parahaemolyticus, V. cholerae, and V. alginolyticus. Meanwhile, 100% of V. parahaemolyticus and V. alginolyticus isolates were completely resistant to Penicillin G and Bacitracin, whereas 100% of V. cholerae isolates exhibited resistance to Penicillin G. The Multiple Antibiotic Resistance (MAR) indices of all isolates ranged from 0.11 to 0.33. The presence of isolates with MAR indices higher than 0.2 suggests potential contamination from sources with high antibiotic usage, such as wastewater or nearby agricultural and aquaculture activities. The findings highlight widespread antibiotic resistance among Vibrio spp., likely due to excessive antibiotics use in aquaculture settings. Additionally, virulence profile of each Vibrio spp. isolates was performed. While pathogenic potential is exhibited by some isolates, others lack key virulence genes associated with pathogenicity. All V. parahaemolyticus isolates showed the presence of tlh, toxR, and toxS genes, whille all V. cholerae isolates were positive with toxS, toxR, rtxA, and rtxC genes. None of the V. alginolyticus showed the presence of the nine tested virulence genes. However, given the high frequency of horizontal gene transfer among bacterial populations, continuous and comprehensive monitoring is crucial to prevent the spread of virulence genes between pathogenic and non-pathogenic strains. Therefore, continuous efforts to obtain more data on antibiotic resistance and bacterial virulence profiles in Sarawak is crucial for effective disease management and sustainable aquaculture practices.